Surface glycoproteins of the recently identified African Henipavirus promote viral entry and cell fusion in a range of human, simian and bat cell lines - (:unkn) unknown (My University, 2014)
The recent discovery of a wide range of henipavirus-like viruses circulating in Megabats in Africa raises the question as to the zoonotic potential of these pathogens given the high human mortality rates seen with their pathogenic relatives Nipah virus and Hendra virus. In the absence of cultured infectious African Henipavirus we have performed experiments with recombinant F and G glycoproteins from the representative African Henipavirus strain M74a aimed at estimating its cellular tropism and capacity to use similar receptors to its highly pathogenic counterparts. The ability of the M74a virus G surface protein to use the ubiquitous Ephrin B2 host cell receptor and its heterologous cross-compatibility with Nipah virus could be expected to impart upon this virus a reasonable potential for species spillover, although differences in fusion efficiency seen with the M74a virus F protein in certain cell lines could present a barrier for zoonotic transmission.
Keywords: African Research